Determinants of Tourist Satisfactory and Unsatisfactory Experiences in Nature-based Tourism Destinations: A Thematic Analysis - Taebenu, Melianus; Letor, Yulia M. K. (International Journal of Applied Sciences in Tourism and Events, 2024)
Tourists play a central role in the tourism industry, serving as the primary drivers of demand that generates economic activities and growth in this industry. This study focuses on understanding the key factors influencing tourist satisfaction and dissatisfaction in nature-based tourism destinations. Fatumnasi, a remote, emerging tourism destination in South-Central Timor, Indonesia, was chosen as the study site. A qualitative approach was utilized in this study.  Data was collected through semi-structured interviews with 17 participants.  A thematic analysis approach was employed to identify and interpret recurring themes within the data, systematically categorizing both positive and negative experiences shared by participants. This process captured specific factors that shaped tourist satisfaction and dissatisfaction, highlighting what aspects of the destination were most valued and where improvements are needed. The finding of this study reveals that tourist satisfaction toward the Fatumnasi tourism destination is primarily driven by the breathtaking natural scenery, biodiverse hotspots, and value for money. In contrast, unsatisfactory experiences were attributed to issues related to poor accessibility and infrastructure, insufficient pre-trip information, and environmental degradation, which indicates a need for improvements in these areas to better meet tourist satisfaction.